Physiological impact of surgical masks and N95 masks on obese operating room staff - Chuanyu Fang; Yanzhe Ba; Yuanlei Gao; Yu Liu; Shaozhong Yang (Scientific Reports)
Abstract This study aimed to determine whether wearing N95 masks for 4 h significantly affected physiological indicators in obese operating room staff compared to surgical masks (SMs). In this randomized crossover trial, the physiological impacts of wearing SMs and N95 masks for 4 h was analysed among 20 obese operating room staff. The data were connected to a nasal sampling tube using the Capnostream 20p monitor. The primary outcome was the change in venous carbon dioxide partial pressure (PvCO2) levels at 4-hour intervention. Secondary outcomes included venous oxygen pressure (PvO2), bicarbonate (HCO3 −), pH levels, end-tidal carbon dioxide partial pressure (PetCO2), peripheral oxygen saturation (SpO2), respiratory rate (RR), pulse rate (PR) and blood pressure after mask intervention. Dyspnoea, palpitations, headache were assessed with the visual analogue scale (VAS) score. N95 masks had a statistically significant rather than clinically significant impact on PvCO2 (mean [95% CI], 1.4 [0.8, 1.9], P < 0.001) and RR (0.6 [0.1, 1.1)], P = 0.023) changes compared with SM. The three subjective VAS scores of the N95 group showed significantly increased than SM group after 2 h. In conclusion, obese operating room staff continuously wearing SM or N95 masks 4 h showed almost no difference in physiological impacts. Trial registration NCT05950256, 18/07/2023.